Characterization of the Betaherpesviral pUL69 Protein Family Reveals Binding of the Cellular mRNA Export Factor UAP56 as a Prerequisite for Stimulation of Nuclear mRNA Export and for Efficient Viral Replication - Zielke, Barbara (American Society for Microbiology (ASM), 2011)
UL69 of human cytomegalovirus (HCMV) encodes a pleiotropic transactivator protein and has a counterpart in every member of the Herpesviridae family thus far sequenced. However, little is known about the conservation of the functions of the nuclear phosphoprotein pUL69 in the homologous proteins of other betaherpesviruses. Therefore, eukaryotic expression vectors were constructed for pC69 of chimpanzee cytomegalovirus, pRh69 of rhesus cytomegalovirus, pM69 of murine cytomegalovirus, pU42 of human herpesvirus 6, and pU42 of elephant endotheliotropic herpesvirus. Indirect immunofluorescence experiments showed that all pUL69 homologs expressed by these vectors were localized to the cell nucleus. Coimmunoprecipitation experiments identified homodimerization as a conserved feature of all homologs, whereas heterodimerization with pUL69 was restricted to its closer relatives. Further analyses demonstrated that pC69 and pRh69 were the only two homologs that functioned, like pUL69, as viral-mRNA export factors. As we had reported recently that nucleocytoplasmic shuttling and interaction with the cellular DExD/H-box helicases UAP56 and URH49 were prerequisites for the nuclear-mRNA export activity of pUL69, the homologs were characterized with regard to these properties. Heterokaryon assays demonstrated nucleocytoplasmic shuttling for all homologs, and coimmunoprecipitation and mRNA export assays revealed that the interaction of UAP56 and/or URH49 with pC69 or pRh69 was required for mRNA export activity. Moreover, characterization of HCMV recombinants harboring mutations within the N-terminal sequence of pUL69 revealed a strong replication defect of viruses expressing pUL69 variants that were deficient in UAP56 binding. In summary, homodimerization and nucleocytoplasmic shuttling activity were identified as conserved features of betaherpesviral pUL69 homologs. UAP56 binding was shown to represent a unique characteristic of members of the genus Cytomegalovirus that is required for efficient replication of HCMV.